Factors determining attitude among non-Malays to join the army in Malaysia - D’Silva, Jeffrey Lawrence; Dahalan, Dzuhailmi; Ismail, Ismi Arif; Abu Samah, Asnarulkhadi; Kamarudin, Nurul Akhtar (Human Resource Management Academic Research Society, 2022)
Desirably the defense of any nation should encompass citizens from the different ethnic groups as this marks greater patriotism and diversity in the armed forces. Malaysia is targeting to achieve a higher number of non-Malays as army recruits to overcome the low number of non-Malays in this sector. The main aim of this study is to determine the level of attitude among non-Malays to enlist in the Malaysian Armed Forces and its’ influencing factors. This is a quantitative study involving a sample size of 1,033 non-Malay students studying in secondary schools in Malaysia. The instrument was developed based on the previous literature. SPSS was used for the purpose of descriptive and inferential analysis. The study found that the attitude among non-Malays to join the armed forces is at a moderate level. Based on the findings, the study recommends more awareness programs conducted by successful non-Malay army officers to be held at the community level that will further expose and entice young non-Malays to join the army.